Solve. 5x^2 - 3x = (5x^2 - 7x) + (8x - 2)

Solve. 5x^2 - 3x = (5x^2 - 7x) + (8x - 2)

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

A. x = -2
B. x = 2
C. x = -1/2
D. x = 1/2

collect like terms on the right hand side

remove the parenthesis first to remove the sign of grouping. .

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.